Population‐based assessment of heartburn in urban Black Americans. Issue 6 (13th December 2012) - Friedenberg, F. K.; Makipour, K.; Palit, A.; Shah, S.; Vanar, V.; Richter, J. E.
Summary. Prevalence data for heartburn in the urban Black American community is lacking. In order to estimate prevalence for this community, we analyzed data from an ongoing cohort study in progress at our hospital. Comprehensive interviews allowed for exploration of factors associated with heartburn. Complex, stratified sampling design was the method used. Survey invitations are hand‐delivered to random blocks in a single zip code tabulation area. One member per eligible household is invited to complete a computer‐based survey. Heartburn was defined as ≥3 days/week of symptoms as defined by the Montreal Definition and Classification of gastroesophageal reflux disease. Scaling and weighting factors were utilized to estimate population level prevalence. Multivariate logistic regression was used to identify independent predictor variables for heartburn. Enrolled 379 participants corresponding to a weighted sample size of 22 409 (20 888–23 930) citizens. Demographic characteristics of the sample closely matched those of the entire targeted population. Overall, the weighted prevalence of heartburn ≥3 times per week was 17.6% (16.4–18.8%). Variables independently associated with heartburn were body mass index, daily caloric and fat intake, diabetes mellitus (odds ratio = 2.95; 2.59–3.36), cigarette smoking, and alcohol consumption (odds ratio = 2.55; 2.25–2.89). Factors inversely associated included illicit drug use and increased physical activity. Waist : hip ratio showed no relationship. The prevalence of heartburn ≥3 times per week is high in the Black American community. Adverse lifestyle behaviors showed particularly important associations. Our study needs to be replicated in other communities with similar demographics.